Effectiveness of Recombinant Human Growth Hormone Therapy for Children With Phelan-McDermid Syndrome: An Open-Label, Cross-Over, Preliminary Study - Li, TianXiao; Xie, Ruijin; Zhao, Jinling; Xu, Hua; Cui, Ying; Sun, Chenyu; Wang, Chunhong; Liu, Yueying (Frontiers in Psychiatry, 2022)
Background: Phelan-McDermid syndrome (PMS), also known as the 22q13.3 deletion syndrome, is a rare neurodevelopmental syndrome with approximately 2800 patients reported worldwide. Previous pilot study demonstrated that IGF-1 could significantly improve in both social impairment and restrictive behaviors of the patients. However, most of the patients in the developing countries like China cannot afford the high cost of using IGF-1. Our research team speculated that rhGH might serve as a low-cost and more accessible treatment for PMS. Methods: A total of six children with PMS were enrolled in in this pilot study. The children were randomly divided into two different groups. Group A received placebo followed by rhGH, while group B was treated with rhGH first. Neuropsychological and behavior assessments of the patients were performed before the stage I of study and three months after the intervention of stage I. After a four-week period of washout, these assessments were conducted again before the stage II of study and three months after the intervention of stage II. Serum insulin-like growth factor-1 (IGF-1) and insulin-like growth factor binding-protein (IGFBP)-3 were also evaluated monthly during the intervention phases of the pilot study Results: Compared with the placebo, rhGH treatment significantly decreased subscale scores of GDS (P <0.0083) and trended to improve the total scores of GDS (P <0.05), while the total scores and subscale scores of SC-ABC significantly decreased (P <0.0085) following three-months rhGH treatment. The similar results were also observed in comparison with baseline. Compared with the baseline, the level of serum IGF-1 and IGFBP-3 increased significantly (P < 0.05) following three-months rhGH treatment, while the placebo group had no significant impact on serum IGF-1 and IGFBP-3 (P > 0.05). One child developed skin allergy the day after the first rhGH treatment, which were resolved later. Conclusions: In summary, this pilot study involving six PMS children patients reveals that rhGH has a positive treatment effect on PMS. These results encourage the undertaking of a large, randomized placebo-controlled trial to conclusively prove rhGH efficacy and tolerability in PMS, thereby promoting it as a low-cost, more accessible treatment for PMS, as compared to IGF-1.